Comparison Of Globoid And Cylindrical Shearer Drums? Loading Performance - M. Ayhan (The Southern African Institute of Mining and Metallurgy, 2006)
Drums of a modern longwall shearer are manufactured to include various constructional features conveying extracted material onto the face conveyor as efficiently as possible. Designing a drum with a conical shell or with reduced vane length, consequently with a stepper vane angle, is the most widely employed method in an attempt to increase loading efficiency. This study compares loading performances of two such drums, one having a conical shell with modified loading vanes, the other with a cylindrical shell with reduced vane length. Firstly, the loading performances of drums are predicted and the maximum haulage rate attainable with the drums are calculated. Then the performances of drum are compared by long-term comprehensive underground trials with coal shearers under similar conditions during the production operation of Park Termik Cayirhan coalmine in Turkey. Although higher loading performance is predicted for cylindrical drums, the in situ trials point out that Globoid drums have a slightly higher loading performance than cylindrical drums. Furthermore, the relationship between operational variables, i.e. extraction height, sumping depth, haulage rate and in situ loading performance, were investigated statistically on the basis of data gathered during the underground trials. Keywords: longwall mining, shearer drums, loading performance.